2018
DOI: 10.1016/j.jadohealth.2017.11.293
|View full text |Cite
|
Sign up to set email alerts
|

Linking Patterns of Substance Use With Sexual Risk-Taking Among Female Adolescents With and Without Histories of Maltreatment

Abstract: This study is the first to determine the specific patterns of substance use that are more strongly related to sexual risk-taking for maltreated female adolescents. By doing so, this study demonstrates how a person-centered approach can facilitate our understanding of how to best leverage sexual risk-taking prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Because different forms of adolescent risk behaviors often co-occur, use of latent class analysis (LCA) as a statistical method to identify subgroups/classes within a population is increasingly used in studies involving adolescent risk behaviors. [26][27][28] However, we are unaware of any studies that examined multiple adolescent risks simultaneously, in relation to protective factors and sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“…Because different forms of adolescent risk behaviors often co-occur, use of latent class analysis (LCA) as a statistical method to identify subgroups/classes within a population is increasingly used in studies involving adolescent risk behaviors. [26][27][28] However, we are unaware of any studies that examined multiple adolescent risks simultaneously, in relation to protective factors and sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Substance use also increases young women’s risk of further exposure to physical and sexual trauma, and consequently HIV, as substance use often places women in high-risk environments for assault and because it often exacerbates conflict in relationships. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Youths who experience CM are more likely to initiate substance use (SU) earlier, escalate SU more rapidly, meet criteria for a substance use disorder (SUD), and experience relapse following SU treatment compared to their non-maltreated peers (Alvarez-Alonso et al, 2016;Dube, et al, 2006;Mills et al, 2014;Shin et al, 2013;Van Dam et al, 2014). A burgeoning literature has also demonstrated that youth who experience CM are at greater risk of engaging in polysubstance use (polySU; Alvarez-Alonso et al, 2016;Rivera, Bray, Guastaferro, Kugler, & Noll, 2018;Snyder & Smith, 2015), a SU pattern that is itself associated with amplified risk of experiencing an SUD (Moss, Chen, & Yi, 2014). Moreover, polySU also represents a significant risk factor for a number of mental and physical health issues (Hakansson, Schlyter, Berglund, 2011;Jones et al, 2017;Smith et al, 2011;Timko, Han, Woodhead, Shelley, & Cucciare, 2018), making it a pertinent SU pattern to investigate in a population already at elevated risk for poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%